Penerapan Teknik Butterfly Hug Untuk Menurunkan Kecemasan Pada Lansia Di Panti Usia Lanjut ‘Aisyiyah Surakarta - Zalsa Dwi Ramdhani; Siti Rahma Soleman (Pusat Riset dan Inovasi Nasional, 2023)
Background: The prevalence of elderly anxiety at the age of 55-65 years is 6.9%, while at the age of 65-75 years it reaches 9.7% and the age of 75 years and over has a figure of 13.4% Along with the increase in the level of anxiety of the elderly in Indonesia, it is found that the elderly experience many problems both physiological and psychological Problems that often arise in the elderly are anxiety experienced by the elderly in Indonesia is very high, Handling in elderly anxiety can be given one of them with the Butterfly Hug relaxation technique to reduce anxiety levels. Objective: Knowing changes in anxiety levels in the elderly at the 'Aisyiyah Surakarta Elderly Home. Method: This study used a descriptive design on 2 elderly respondents conducted from May 26-28, 2023 at the 'Aisyiyah Surakarta Elderly Home with each respondent given an intervention for 3 consecutive days. The instrument used was the Geriatric Anxiety Inventory (GAI) observation Results: The level of anxiety before implementation on both respondents was included in the moderate anxiety category with the 1st respondent scoring 10 and the 2nd respondent scoring 9, Then after the application, the anxiety level of the two respondents fell into the mild anxiety category with the 1st respondent scoring 3 and the 2nd respondent scoring 4. Conclusion: The application of the Butterfly Hug technique is able to reduce anxiety levels in the elderly at the 'Aisyiyah Surakarta elderly home.